Demographic Characteritics of Relapsing Schizophrenic Patients - Gustira, Erika; Nauli, Fathra Annis; Amir, Yufitriana (Jurnal Keperawatan Soedirman, 2021)
Schizophrenia is a disease that affects the brain and causes strange, disturbing thoughts, perceptions, emotions, movements and behavior. Recurrence is a term that relatively reflects the worsening of symptoms or behaviors that endangers patients and or their environment. This study aims to analyse the characteristics of schizophrenia patients with recurrence at the Tampan Mental Hospital of Pekanbaru With quantitative descriptive research design. The research sample were 167 respondents taken based on inclusion criteria by using purposive sampling technique. The analysis method used is univariate analysis. The results showed clinical characteristics of 167 respondents, received the majority of the respondents lived with the family 85 respondents (50.9%). Medical diagnosis of most schizophrenia paranoid 121 respondents (72.5%). Diagnosed for 1-5 years 82 respondents (49.1). Based on the most recurrence factor caused by treatment 120 respondents (71.9%). Based on the most predisposition factor caused by genetic 74 respondents (44.3%). while the precipitation factors resulting from family and socioeconomic 51 respondents (30.5%). Based on the results of this study can be concluded that the recurrence in schizophrenia patients is caused by a variety of conditions, so that it takes appropriate treatment and according to the characteristics Patients.